Strategi Menuju Perdamaian Berkelanjutan Di Masyarakat Multikultural Melalui Proses Pendidikan Di MA An-Nawawiyah Jepara - Ginanjar, Slamet (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2024)
This study aims to explore the educational strategies implemented at MA Anawawiyah Jepara in creating sustainable peace in a multicultural society. Through a qualitative approach with a case study design, this study collected data through interviews, focus group discussions, and direct observation. The results showed that educational programs that integrate the values ​​of tolerance and cooperation significantly increase intercultural understanding among students. Activities such as intercultural dialogue, Cultural Day, and group-based projects contribute to the formation of mutual respect and solidarity among students. Despite challenges, such as the need for additional training for teachers, this study confirms that peace education at MA Anawawiyah Jepara has had a significant positive impact and can be a model for other educational institutions in their efforts to create a more peaceful and tolerant society.